Correlation between microstructure parameters and anti-cancer activity of the [Mn0.5Zn0.5](EuxNdxFe2-2x)O4 nanoferrites produced by modified sol-gel and ultrasonic methods. Issue 6 (15th April 2020) - Almessiere, M.A.; Trukhanov, A.V.; Khan, F.A.; Slimani, Y.; Tashkandi, N.; Turchenko, V.A.; Zubar, T.I.; Tishkevich, D.I.; Trukhanov, S.V.; Panina, L.V.; Baykal, A.
Abstract: [Mn0.5 Zn0.5 ](Eux Ndx Fe2-2x )O4 ferrite nanoparticles (FNP) were obtained by ultrasonic (USM) and sol-gel (SGM) methods. It was observed that SGM allows us to produce nanoparticles with the average crystal size of 10–40 nm and the specific surface area of 5–7.5 × 10 4  m 2 /g with a strong correlation between the chemical composition (x) and the crystal size distribution. At the same time using USM, we obtained nanoparticles with the average crystal size of 3–15 nm and the specific surface area of 1.5–1.7 × 10 5  m 2 /g without a strong correlation between Eu/Nd concentration and the crystal size distribution. The specific surface area and average crystal size are the main factors determining the antiproliferative activity of FNP. The anti-cancer activity of FNP was investigated both on cancerous cells, human adenocarcinoma cells and human colorectal carcinoma cells. It was established that samples obtained using USM were more effective in producing cytotoxic effects on cancer cells. Thus, we confirm a strong correlation between the main microstructure parameters for [Mn0.5 Zn0.5 ](Eux Ndx Fe2-2x )O4 ferrite nanoparticles.